2017
DOI: 10.1080/08964289.2017.1288607
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interventions to Reduce Infections in Pediatric Long-term Care Facilities: The Keep It Clean for Kids Trial

Abstract: Children in pediatric long-term care facilities (pLTCF) represent a highly vulnerable population and infectious outbreaks occur frequently, resulting in significant morbidity, mortality, and resource use. The purpose of this quasi-experimental trial using time series analysis was to assess the impact of a 4-year theoretically based behavioral intervention on infection prevention practices and clinical outcomes in three pLTCF (288 beds) in New York metropolitan area including 720 residents, ages 1 day to 26 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 50 publications
(59 reference statements)
2
22
0
2
Order By: Relevance
“…Additionally, previous studies have suggested that behavioural changes are important in the improvement of HH [25][26][27] and that this improvement took time, sometimes years. Similar results were reported from a 6-year initiative in a tertiary teaching hospital [28] and a 4-year initiative in a paediatric long-term care facility [29].…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, previous studies have suggested that behavioural changes are important in the improvement of HH [25][26][27] and that this improvement took time, sometimes years. Similar results were reported from a 6-year initiative in a tertiary teaching hospital [28] and a 4-year initiative in a paediatric long-term care facility [29].…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, previous studies have suggested that behavioural changes are important in the improvement of HH [21][22][23] and that this improvement took time, sometimes years. Similar results were reported from a 6-year initiative in a tertiary teaching hospital [24] and a 4-year initiative in a long-term care facility [25]. Welsh et al…”
Section: Discussionsupporting
confidence: 79%
“…Prohibitions or provisions for selling are not provided by the school. So, bringing the homemade and healthy food from home is considered as best solution to practice the clean and healthy behavior especially for to keep consuming a healthy food in the future (Larson et al, 2017). The other lowest score was obtained from the low frequency of measuring the weight and height of the child.…”
Section: Resultsmentioning
confidence: 99%